Las sociedades ancestrales del Valle Central de la actual Costa Rica (1000 a.C.-1550 d.C.) - Arias Quirós, Ana Cecilia; Murillo Herrera, Mauricio (Revista de historia., 2014)
The presented document is an actualized synthesis of the Central Valley Archeology with a specific mention to the occidental sector. It details profusely the substantive information derived from scientific investigations, made by different specialists, which allow us to talk assertively of the lifestyles of the ancient inhabitants of this territory. We also mentioned about the type of population that should have had the Occidental sector of the Central Valley, with emphasis in the environmental characteristics that allowed, along cultural decisions, to develop more diverse and complex societies. We had used theoretical elements that allowed us to amalgamate that substantive information and in consequence to collaborate in the reconstruction on these ancient human groups, that inhabited our ancestral territory. This document is also, a tribute to San Jose, our Capital in its two hundred anniversary of holding the status of City, this sometimes chaotic city is holder of an ancient history, diverse, multicausal, the same as now, it sheltered human groups capable of interact with nature as from a determined social-cultural production.